Status of rehabilitation of the dizzy patient in France: focus on vestibular physiotherapy. (4th March 2023) - Xavier, Frédéric; Chouin, Emmanuelle; Montava, Marion; Tighilet, Brahim; Lavieille, Jean-Pierre; Chabbert, Christian
Abstract: Purpose: This study was carried out within the framework of a research on the non-medicinal managment of the dizzy patient. In order to carry out an inventory of vestibular rehabilitation practices in France, we conducted this research among practitioners recognized in this exercise. Materials and Methods: We conducted a survey using a thoretical questionnaire submitted to the whole community of french vestibular physiotherapists. We benefited from a statistically signifiant recruitment of this population and we were able to perform a statistical treatment of the data in order to answer questions concerning the current practice of vestibular rehabilitation. Results: We observed autonomous therapeutic behaviours and the development of the practices of French vestibular physiotherapist which can be considered like a 'clinician of the vertigo re-education'. Continuing education nevertheless remains heterogeneous, and a national diploma resulting from standardised and adapted teaching does not sanction vestibular rehabilitation. Conclusion: This study is a 'snapshot' of the vestibular physiotherapist profession in France in 2019. It reveals a population of dynamic practitioners questioning their action in terms of health and their role regarding their prescribers, colleagues and other paramedical professions (osteopaths, orthoptists and psychomotricians).